Influence of polarization on the electromechanical properties of GaN piezoelectric semiconductive ceramics - Zhao, M.; Ma, S.; Lu, Chunsheng; Fan, C.; Qin, G. (Elsevier Science Ltd, 2018)
By using three-point bending tests and numerical simulation, influence of polarization on the electromechanical properties of GaN piezoelectric semiconductive ceramics (PSCs) were investigated in this paper. The results show that the piezoelectricity of GaN PSCs can be attained through a special polarization treatment. For polarized samples under loading, because piezoelectric polarization charges and the electric field are concentrated at high-strain positions, their bending strength increases by 7%. Polarization results in a nearly 55% improvement of the electrical current transport capacity. Due to piezoelectricity, the electric displacement of polarized samples is also largely changed. It is shown that there is a strong correlation between polarization and electromechanical properties of PSCs. These findings highlight the influence of polarization on the electromechanical performance of PSCs, and also imply some potentials for their applications.